Effects of Visceral Fat Accumulation Awareness on a Web-Based Weight-Loss Program: Japanese Study of Visceral Adiposity and Lifestyle Information—Utilization and Evaluation (J-VALUE). (24th April 2013) - Sakane, Naoki; Dohi, Seitaro; Sakata, Koichi; Hagiwara, Shin-ichi; Morimoto, Toshihisa; Uchida, Takanobu; Katashima, Mitsuhiro; Yanagisawa, Yoshiko; Yasumasu, Takeshi; Study Group, J-VALUE
Abstract : A reduction of visceral fat is important for improvement of metabolic risk. This study was designed to compare the effects of a web-based program alone or together with measurement and self-awareness of accumulated visceral fat in Japanese workers. A new noninvasive device to measure visceral fat accumulation was introduced, and efficacy on weight-loss and improvement of healthy behaviors were examined. This study was conducted according to Helsinki declaration and approved by the ethical committee of Japan Hospital Organization, National Kyoto Hospital. Two-hundred and sixteen overweight and obese males with BMI of more than 23 participated from 8 healthcare offices of 3 Japanese private companies. Subjects were randomly allocated into control group, Web-based weight-loss program (Web), or Web + Visceral fat measurement group (Web + VFA). Eighty-one percent of participants completed the study. Reductions of body weight, waist circumference, and BMI were the largest in Web + VFA group, and the differences between groups were significant by ANOVA. Improvements of healthy behaviors were the largest in Web + VFA group, and the differences of healthy eating improvement scores between Web + VFA and control groups were significant. Our findings suggest that measurement and awareness of visceral fat are effective in weight reduction in overweight and obese males in the workplace.